Patella vulgata and Spirobranchus (Pomatoceros) lamarcki genonme and transcriptome assemblies. - Shimeld, S (University of Oxford, 2015)
The data are associated with the publication: Draft genome assemblies and predicted microRNA complements of the intertidal lophotrochozoans Patella vulgata (Mollusca, Patellogastropoda) and Spirobranchus (Pomatoceros) lamarcki (Annelida, Serpulida). The data were generated to allow genome-wide prediction of microRNA genes and hence allow hypotheses concerning microRNA gene loss and homoplasy to be tested. The data are transcriptome and genome assemblies built from raw sequence data derived from the Illumina GAII and Illumina Hi-Seq2000 sequencing platforms. The raw data pertaining to the genome assemblies for both species are available from the public NCBI Short Read Archive under accession numbers NCBI SRA SRP055158 and SRP055157. Additional information on the transcriptome assemblies and associated data can be found in Werner et al (2012) Mar. Biotechnol. DOI 10.1007/s10126-012-9481-0., and in Kenny and Shimeld (2012) Dev. Genes. Evol. DOI 10.1007/s00427-012-0416-6. The data are all is fasta format (with files appended with .fas or .fa). One is zipped.